Preliminary Experiments on Electrical Fishing in Fresh Water - NAMBOODIRI, K. SREEDHARAN (Fishery Technology, 1966)
Fishing using electricity is a new technique and is still in the experimental stages in many of the advanced countries. While no published records are available in India, considerable work has been done in Germany (Mayer Waarden, 1953, 1954a, 1954b, 1955, 1957; Hattop, 1957, 1958a, 1958b; Kreutzer, 1951, 1954; Denzer, 1954, 1956; Halsband, 1955, 1956), United States (Smith, 1955a, 1955b, 1955c; Halton et. al., 1954; Lennon and Parker, 1958; Wathwe et. al., 1964), USSR (Shentiakov, 1963; Shentiakov et. al., 1959; Nikonorov et. al., 1959; Nikoronov Ivan, 1964; Badamshin et. al., 1964), Canada (Smith and Sanders, 1954), Newfoundland (Murray, 1958), United Kingdom (Mck-Bary, 1956; Dickson, 1954). These papers mainly deal with the behaviour of the fish in the electrical field, the physiological effects of electrical current on fishes, methods of electrofishing, electric fencing etc.